Analisis Rancang Bangun Sistem Informasi Keuangan Berbasis Website pada CV. Pusat Handicraft Analysis of Financial Information System Website Based on CV. Pusat Handicraft - Choirurrozi, Choirurrozi; Arum, Khorifah; Khomeini, Zulhaq (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2023)
CV. Pusat Handicraf is a manufacturing company with a broad target market, many transactions make financial records important. To improve the quality of management, a financial technology that is capable of running automatically and providing accurate information is needed. This study aims to analyze the needs of financial information systems and design a system that is able to assist the process of planning, controlling, and evaluating company finances by utilizing the website. The research method used in this study uses a qualitative research method with a descriptive approach. The data used were obtained using observation and interview methods. This research is composed of the stages of business process and resource analysis, needs analysis, financial information system design, feasibility testing, implementation of financial information systems and conclusions. The result of this research is the creation of a website-based financial information system that meets needs and is able to assist in providing financial information that can be used as material for planning, controlling and evaluating finances as well as supervising all transactions made